A practical bistatic passive radar system for use with DAB and DRM illuminators - Coleman, C.J.; Watson, R.A.; Yardley, H. (2008 IEEE Radar Conference, 2008)
Digital broadcasts provide powerful illuminators of opportunity with waveforms that produce excellent radar ambiguity functions. An experimental program to investigate the possibility of such broadcasts for target tracking radar is described. In addition, the atmospheric monitoring possibilities for such broadcasts are discussed.